Perilaku petani padi terhadap risiko usahatani pada suku yang berbeda di Jawa Timur: Rice farmers' behavior towards farming risks in different tribes in East Java - Murtadlo, Kholid (Fakultas Pertanian Universitas Yudharta Pasuruan, 2023)
Introduction: The agricultural sector is a sector that depends on natural conditions so that uncertainty and risk in farming always occurs. The source of risk is predicted to continue to grow which greatly affects the total agricultural yield. Farming risk consists of production risk and price. Production risk is related to production uncertainty. Price risk is related to price fluctuations that cause losses to farmers because prices are difficult to predict. Indonesia is known for its diversity with nearly 300 ethnicities. Each ethnic group has different characteristics in behavior, language and customs. This difference is possible to influence decisions in managing a business, including in dealing with farming risks. This study attempts to analyze the behavior of rice farmers on the risk of farming among various ethnic groups in East Java and factors that influence farmer behavior towards farming risk. Methods: This research was conducted in Pamekasan, Ngawi and Pasuruan, where these three districts represent Javanese, Madurese, and Madura-Javanese ethnic assimilation. The data used are primary data collected from 49 respondents in Pamekasan Regency, 72 in Ngawi Regency and 65 in Pasuruan Regency so that a total of 186 respondents using the cluster sampling approach. Farmers' behavior towards farm risk was analyzed using the Just and Pope risk function model with the utility function approach, while the analysis of factors that influenced behavior towards farm risk was carried out using multiple regression. Results: The results of the analysis show that the behavior of rice farmers in Pamekasan District with Madura ethnic risk seekers, in Pasuruan Regency is a risk averse and in Ngawi Regency is a risk seeker. Conclusion: Regression analysis shows that differences in ethnicity of farmers affect the way rice farmers deal with farming risks